IoT Platform for Monitoring Systems Water pH in the Freshwater Fish Cultivation Process - Kurnia, Deni; Riyadi, Slamet; Dewi, Deshinta Arrova; Suprianto, Adolf Asih; Rahmadani, Olivia (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2024)
This study describes the implementation of the Internet of Things using the MQTT protocol and mosquitto as a broker combined with a 2x16 LCD for a pH monitoring system in a freshwater fish farming system at BPBIAT Purwakarta, West Java, Indonesia. To obtain accurate data, the calibration process is carried out in several stages, including using buffer 6.8 and distilled water. The calibration results on the 6.8 buffered liquid sample mean that the data obtained are appropriate, while the aquades obtained a value of 7.73, this is due to the storage factor of the distilled water so that it can change the pH value. The final result of the research shows that the data that appears online on the Node-Red dashboard is the same as that which appears locally on the 2x16 LCD. This means the MQTT protocol is working fine. The data displayed on the Node-Red UI is sent periodically every 30 minutes. The consideration is that, during the experiments, the pH value of the water did not change significantly beyond the range of 6.5-8.5. This data illustrates that the pH quality of the water for freshwater fish farming at BPBIAT is ideal for use.